Comparison of lower limb kinematics during early and late phases of 2km time trial on stationary rowing ergometer among male national rowers - Zahiran, A.; Zainuddin, F. L.; Shaharudin, S. (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: In this study, we evaluated the kinematics of lower limb during early and late phases of 2km time trial on stationary rowing ergometer among Malaysian male rowers. Methods: Seventeen national-level rowers voluntari-ly participated. Three dimensional lower limb kinematics data were collected to represent the first 400 m (i.e., early) and the last 400m (i.e., late) phases of 2km time trial on a stationary ergometer. The kinematics data at sagittal, frontal and transverse planes of dominant leg during catch and finish positions were compared across early and late phases of the time trial using paired T-test. Results: The kinematics of lower limb joints at three planes were not significantly different during early versus late phases of 2km time trial among male senior rowers except for hip flexion at finish (p=0.411), ankle rotation at catch (p=0.779) and ankle abduction at finish (p=0.677). Conclusion: Lower limb kine-matics particularly the hip flexion, ankle rotation and ankle abduction may change across early and late phases of 2km time trial due to fatigue. Coaches and rowers should monitor these motions during fatiguing rowing piece and develop necessary injury prevention measures.